Portal Vein Thrombosis Experiences in a Tertiary Neonatal Intensive Care Unit - Kandemir, İbrahim; Yaman, Akan; Alp Ünkar, Zeynep (Cerrahpaşa Medical Journal, 2023)
Objective: The aim of the study was to present the clinical and descriptive features of patients with portal vein thrombosis. Methods: The study was conducted in a tertiary neonatal intensive care unit in Istanbul, Turkey. We included the patients diagnosed with portal vein thrombosis hospitalized in our neonatal intensive care unit between January 2017 and December 2021, retrospectively. We investigated the birth history, anthropometric measurements, the postnatal day of portal vein thrombosis detected, and clinical history. Results: Nineteen patients (12 male) were eligible for the study. Portal vein thrombosis incidence was 3.9 per 1000 infants admitted to our neonatal intensive care unit. The mean gestational week was 35.1 ± 4.8 weeks. The median birth weight was 2835 g (1335-3250), and the median length was 47 cm (38-50). We detected portal vein thrombosis on median postnatal 13 days. Portal vein thrombosis was in the left portal vein in 84.2% (n = 16) and the main portal vein in 15.8% (n = 3) patients. About 68.4% (n = 12) of the patients had umbilical venous catheter, 47.4% (n = 9) had a history of perinatal asphyxia, 26.3% (n = 5) had necrotizing enterocolitis, 5.3% (n = 1) had tracheoesophageal fistula + anal atresia, and 5.3% (n = 1) had an omphalocele. In 15.7% (n = 3) of the patients, we detected portal vein thrombosis without any known clinical risk factor on the first postnatal day. About 26.3% (n = 5) of patients underwent anticoagulation treatment. All the thrombosis was re-canalized, except 1 patient. Conclusion: Portal vein thrombosis can be seen on the first postnatal day, even in babies with no perinatal problems. The cases had asphyxia and intra-abdominal operation/necrotizing enterocolitis as risk factors. Portal vein thrombosis incidence was 3.9 per 1000 neonatal intensive care unit admission. Cite this article as: Kandemir İ, Yaman A, Alp Ünkar Z. Portal vein thrombosis experiences in a tertiary neonatal intensive care unit. Cerrahpaşa Med J. 2023;47(2):187-190.